2003
DOI: 10.1046/j.1461-0248.2003.00400.x
|View full text |Cite
|
Sign up to set email alerts
|

Phoenix clones: recovery after long‐term defoliation‐induced dormancy

Abstract: Many long‐lived plants are known to prolong dormancy in response to abiotic stresses such as drought. We are unaware, however, of any reports of plants prolonging dormancy in response to biotic stresses such as herbivory. We monitored 140 putative Solidago missouriensis clones (hereafter ‘clones’) ≥ 13 years before, during and after intense defoliation by the specialist herbivore Trirhabda canadensis. Eight of the clones produced no above‐ground growth in the season following defoliation. Though apparently kil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 39 publications
(56 reference statements)
0
35
0
Order By: Relevance
“…Drought is commonly reported to induce dormancy (Epling and Lewis 1952;Thomas et al 1981;Tyler and Borchert 2002;Kéry et al 2005;Johnson-Groth and Farrar 1993). Inundation (Oostermeijer et al 1992), fire (Abrahamson and Hartnett 1990;Keeler 1991;Coates et al 2006), spring frost days (Shefferson et al 2001) and herbivory (Morrow and Olfelt 2003) are amongst other factors reported to promote prolonged dormancy. Associations with stressful conditions suggest that dormancy is at least partly induced by a shortage of resources such as water, nutrients or energy, although it is not clear whether plants avoid stressful conditions through dormancy or are constrained to be dormant by low resource availability (Lesica and Crone 2007;Morrow and Olfelt 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Drought is commonly reported to induce dormancy (Epling and Lewis 1952;Thomas et al 1981;Tyler and Borchert 2002;Kéry et al 2005;Johnson-Groth and Farrar 1993). Inundation (Oostermeijer et al 1992), fire (Abrahamson and Hartnett 1990;Keeler 1991;Coates et al 2006), spring frost days (Shefferson et al 2001) and herbivory (Morrow and Olfelt 2003) are amongst other factors reported to promote prolonged dormancy. Associations with stressful conditions suggest that dormancy is at least partly induced by a shortage of resources such as water, nutrients or energy, although it is not clear whether plants avoid stressful conditions through dormancy or are constrained to be dormant by low resource availability (Lesica and Crone 2007;Morrow and Olfelt 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown dormancy rates to increase after defoliation (Morrow and Olfelt 2003;Shefferson et al 2005;Ehrlen 2003) and drought (Epling and Lewis 1952;Boeken 1991;Lesica and Steele 1994;Vaughton and Ramsey 2001). Shefferson et al (2005) speculated that dormancy reduced mortality rates following defoliation in an orchid species.…”
Section: Discussionmentioning
confidence: 98%
“…Shefferson et al (2005) speculated that dormancy reduced mortality rates following defoliation in an orchid species. In a study of Solidago clones, Morrow and Olfelt (2003) suggested that dormancy allowed plants to escape the risk of future herbivore attack. In this case, the herbivore in question (a leaf beetle) laid larvae in Solidago clones, and defoliation in one year increased the risk of defoliation in later years.…”
Section: Discussionmentioning
confidence: 99%
“…It is often cued by climate, although the exact controlling mechanisms are not yet understood (Gregg 1991, Shefferson et al 2001, Kéry and Gregg 2004. In the recent literature, it has been suggested to act as a buffering strategy in perennial herbaceous plants because it occurs in response to environmental stress and may decrease the resulting mortality (Morrow andOlfelt 2003, Shefferson et al 2005). However, testing the ''adaptive hypothesis'' for vegetative dormancy remains difficult for three reasons.…”
Section: Introductionmentioning
confidence: 99%